Primary cardiovascular disease-related disability structure in Russian Federation - N. L. Kardakov (Российский кардиологический журнал, 2007)
Detailed, age-specific information on primary cardiovascular disease-related disability dynamics in Russian Federation is presented for 12-year period (1994-2005), including data on coronary heart disease and cerebrovascular disease-related disability. Pensioners are prevalent in primary disabled population, and their percentage grew in 2004-05, due to increased number of Medico-Social Expertise Bureau (MSEB) applications since the Federal Law No. 122-FL on health benefits monetarization was launched (22.08.2004). This information is most useful for the Russian ministries and departments working with primary disability problem.